The phenomenon of inner marriage from the perspective of national marriage law and protection of women - Syahril, Muh. Akbar Fhad; Hasan, Nurhaedah (Priviet Social Sciences Journal, 2025)
This article analyzes unregistered marriage in Indonesia from a national legal perspective, focusing on its impact on the rights of women and children. Applying a normative legal approach, the study reviews statutory law, religious fatwas, and court decisions to clarify that unregistered marriages, while sometimes valid religiously, however lack formal legal recognition under Undang-Undang Perkawinan. This legal gap exposes women to loss of civil rights and leaves children vulnerable to administrative discrimination and social stigma. The discussion also highlights legal developments following Putusan Mahkamah Konstitusi No. 46/PUU-VIII/2010, as well as the influence of local traditions and limited legal literacy. The article concludes by recommending legal reform, community legal education, and integration of customary practices to strengthen protection for affected groups.